Acepções de um currículo de Filosofia - Souza, Mateus Leite de (2021)
This dissertation, entitled "Acceptances of a Philosophy curriculum", demonstrates that there was no contribution from the curricular bases, proposed and offered by the Department of Education of the State of São Paulo (considering their reinsertion in the official curriculum of the State of São Paulo), for the development of the Philosophy discipline in the classroom. It was found that the philosophical attitude is not the main focus of the materials, which end up being an obstacle to the fulfillment of the real function of the discipline. Teaching, therefore, is characterized by the presentation of the history of Philosophy or a work with dispersed themes, with a noticeable historical devaluation and disregard for the contributions that the aforementioned area of knowledge could employ in the school environment. In addition to the devaluation carried out around the subject, there was not, even after its reconsideration in the curriculum, a positive application in the classroom, its importance being increasingly depreciated. Therefore, the intention of this study is to demonstrate how, historically, the devaluation of Philosophy occurred and how students are directly affected in their education. The bibliographical research sought references in the works of authors who believe in the significant work of the discipline in question, such as: Dermeval Saviani, Silvio Gallo, Cipriano Luckesi, Moacir Gadotti, among others. In addition to a historical presentation of the path of Philosophy in Brazil and in the State of São Paulo, which proves the devaluation and absence of the strength of the discipline, this research, through qualitative analysis of interviews provided by students, former students and managers from the public network, demonstrates the gaps left by the discipline in the training of students, with regard to the exercise of citizenship and the absence of the concepts of experience and philosophical experience, as well as other possible contributions in the school and social spheres, according to the proposals of the steering documents.